2015
DOI: 10.1007/s10803-015-2388-7
|View full text |Cite
|
Sign up to set email alerts
|

Maladaptive Behavior in Autism Spectrum Disorder: The Role of Emotion Experience and Emotion Regulation

Abstract: Maladaptive behavior is common in Autism Spectrum Disorder (ASD). However, the factors that give rise to maladaptive behavior in this context are not well understood. The present study examined the role of emotion experience and emotion regulation in maladaptive behavior in individuals with ASD and typically developing (TD) participants. Thirty-one individuals with ASD and 28 TD participants and their parents completed questionnaires assessing emotion experience, regulation, and maladaptive behavior. Compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
98
0
3

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(108 citation statements)
references
References 34 publications
7
98
0
3
Order By: Relevance
“…With regard to the self-report measures, it was examined whether individuals scoring high on autistic traits show a deviant ER pattern. In line with studies on individuals from the clinical population (Samson et al 2012, 2014a, b, 2015a, b), people scoring high on autistic traits reported using fewer adaptive and more maladaptive ER strategies than individuals scoring low on autistic traits. Our results thus demonstrate that similar associations between autistic traits and ER strategies can be found in both a clinical and a non-clinical sample, which is consistent with the broad autism spectrum approach.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…With regard to the self-report measures, it was examined whether individuals scoring high on autistic traits show a deviant ER pattern. In line with studies on individuals from the clinical population (Samson et al 2012, 2014a, b, 2015a, b), people scoring high on autistic traits reported using fewer adaptive and more maladaptive ER strategies than individuals scoring low on autistic traits. Our results thus demonstrate that similar associations between autistic traits and ER strategies can be found in both a clinical and a non-clinical sample, which is consistent with the broad autism spectrum approach.…”
Section: Discussionsupporting
confidence: 72%
“…Mazefsky et al (2014) showed that the more frequent use of maladaptive ER strategies such as rumination by adolescents with ASD was associated with higher levels of anxiety and depression. Focussing on both internalising and externalising psychopathologies in children and adolescents with ASD, stronger reliance on maladaptive (suppression) and weaker reliance on adaptive (reappraisal) ER strategies has shown to be related to higher levels of negative emotion (Samson et al 2015a). These increased levels of negative emotion in turn resulted in maladjusted behaviour, such as impulsivity, truancy, and temper tantrums.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have corroborated the critical role of emotion dysregulation in affective functioning (Mazefsky et al, 2013;Samson et al, 2012Samson et al, , 2015b. Individuals with ASD, compared to TD participants, seem to have a dysfunctional pattern of emotion regulation, characterized by less frequent use of adaptive emotion regulation strategies (goal-directed behaviors, seeking social support, cognitive reappraisal; Jahromi et al, 2012;Rieffe et al, 2011;Samson et al, 2012) and more frequent use of maladaptive strategies (avoidance, venting, expressive suppression; Jahromi et al, 2012;Konstantareas and Stewart, 2006;Samson et al, 2012Samson et al, , 2015aMazefsky et al, 2014).…”
Section: Socio-affective Deficits In Autism Spectrum Disordermentioning
confidence: 89%
“…Individuals with ASD, compared to TD participants, seem to have a dysfunctional pattern of emotion regulation, characterized by less frequent use of adaptive emotion regulation strategies (goal-directed behaviors, seeking social support, cognitive reappraisal; Jahromi et al, 2012;Rieffe et al, 2011;Samson et al, 2012) and more frequent use of maladaptive strategies (avoidance, venting, expressive suppression; Jahromi et al, 2012;Konstantareas and Stewart, 2006;Samson et al, 2012Samson et al, , 2015aMazefsky et al, 2014). Emotion dysregulation in ASD has been linked to increased psychopathology (Mazefsky et al, 2014), lower levels of prosocial peer engagement (Jahromi et al, 2013), and higher levels of maladaptive behavior (Samson et al, 2015b).…”
Section: Socio-affective Deficits In Autism Spectrum Disordermentioning
confidence: 99%
“…But this study used only one moral dilemma per condition and thus generalizability of these results remains to be assessed. This finding is also surprising in the light of evidence for prevalent negative hyperarousal in autistic individuals [60][61][62] , which would make it less likely that they would make utilitarian moral judgments 45,49 . Indeed, another unpublished study did not find any evidence for such increased utilitarian proclivity in ASD (Dr. Geoffrey Bird, personal correspondence).…”
mentioning
confidence: 89%